EXPERT SYSTEM FOR DIAGNOSIS OF DISEASES IN CAT USING THE NAIVE BAYES METHOD - Riky Yoga Perkasa; Nurul Fuad (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
Cats are animals that relieve stress. When a person spends time with a cat, the hormones serotonin, oxytocin and dopamine increase. One of the reasons why cats can relieve stress is purring, that has a frequency level of 25-50 hertz. But cats can also get sick. Researchers took the initiative to create an application to make it easier for users, to be able to diagnosed earlier. The purpose of this application was that it can be an option other than going to an expert, a good accuracy when compared to experts and providing the right solution. Making the application used the Naïve Bayes method as an analysis of cat data from expert sources that produced that symptoms produced appropriate disease with the solution. Implementation users starting from filling in biodata, symptoms, generating diseases and their solutions, and additional features such as disease info and messages. Meanwhile, admin requires a login to use the data management of symptoms, diseases, knowledge base, accounts and messages. The results of the application were explained from the results of the diagnosis which can detect the cats disease from the inputted symptoms, along with other disease options, with a disease comparison value of 91%.